Glycerination as an alternative technique for preserving Vertebrata (Osteichthyes and Reptilia): a proposal for teaching purposes - Ribeiro, Joice Gabriele Rocha; Santos, Alana Ferraz de Melo; Soares, Aléxia David Santos; Rocha, Mariane Amorim; Fraga, Ricardo Evangelista; Queiroz, Tiago Sousa de; Silva, Márcio Borba da (Acta Scientiarum. Biological Sciences, 2024)
Biological specimens are essential for teaching, research, and extension, although they require effective preservation. The glycerination technique stands out for allowing specimens to be preserved dry, which saves costs and facilitates handling due to specimen malleability. We sought to establish an optimal glycerination protocol for fish and reptiles for teaching purposes. Several fixatives were tested, including formalin at different concentrations and Transeau solution. The fixation process involved injecting a 50% fixative and 50% double-distilled glycerin solution into the specimen, followed by immersion in the same fixative. After seven days animals were washed, partially dried, and subsequently immersed for 60 days in double-distilled glycerin with camphor. The specimens were then kept in air-conditioned environments with a dehumidifier during a 30-day drying period. A 3% formalin solution was found to be the most efficient, guaranteeing the mental 10 some of the specimens’ colors, and their malleability. This study contributes to the optimization of glycerination preservation and effectively preserving fish and reptile specimens for teaching purposes while reducing handling risks.